The anti-inflammatory and protective role of interleukin-38 in inflammatory bowel disease - Inatomi, Osamu; Andoh, Akira; Imai, Takayuki; Ohno, Masashi; Nishida, Atsushi; Kawahara, Masahiro; Chatani, Motoharu; Hoshino, Tomoaki (Journal of Clinical Biochemistry and Nutrition, 2022)
Interleukin (IL)-38 exerts an anti-inflammatory function by binding to several cytokine receptors, including the IL-36 receptor. In this study, we evaluated IL-38 expression in the inflamed mucosa of patients with inflammatory bowel disease (IBD) and investigated its functions. IL-38 mRNA expression in endoscopic biopsy samples was evaluated using quantitative PCR. IL-38 protein expression was analyzed using immunohistochemical technique. Dextran sulfate sodium-induced colitis was induced in C57BL/6 background IL-38KO mice. The IL-38 mRNA and protein expression were enhanced in the active mucosa of ulcerative colitis, but not in Crohn’s disease. The ratio of IL-36γ to IL-38 mRNA expression was significantly elevated in the active mucosa of UC patients. Immunofluorescence staining revealed that B cells are the major cellular source of IL-38 in the colonic mucosa. IL-38 dose-dependently suppressed the IL-36γ-induced mRNA expression of CXC chemokines (CXCL1, CXCL2, and CXCL8) in HT-29 and T84 cells. IL-38 inhibited the IL-36γ-induced activation of nuclear-factor kappa B (NF-κB) and mitogen-activated protein kinases in HT-29 cells. DSS-colitis was significantly exacerbated in IL-38KO mice compared to wild type mice. In conclusion, IL-38 may play an anti-inflammatory and protective role in the pathophysiology of IBD, in particular ulcerative colitis, through the suppression of IL-36-induced inflammatory responses.